Clinical Profile and Risk Factors for Cardiac Death in Pediatric Patients With Primary Dilated Cardiomyopathy at a Tertiary Medical Center in China - Wang, Yan; Han, Bo; Fan, Youfei; Yi, Yingchun; Lv, Jianli; Wang, Jing; Yang, Xiaofei; Jiang, Diandong; Zhao, Lijian; Zhang, Jianjun; Yuan, Hui (Frontiers in Pediatrics, 2022)
Aim: We sought to identify the clinical characteristics and risk factors for cardiac mortality in pediatric patients with primary dilated cardiomyopathy (DCM) in China. Methods: A total of 138 pediatric patients who were consecutively diagnosed with primary DCM from January 2011 to December 2020 were included. We assessed patients’ clinical symptoms and performed laboratory examinations, electrocardiography, and echocardiography. Results: Of these patients, 79 (57%) had severe systolic dysfunction (left ventricular ejection fraction of <30%), 79 (57.2%) developed DCM before 12 months of age, 62 (45%) were male, 121 (87.7%) presented with advanced heart failure (cardiac functional class III/IV), and 54 (39.1%) presented with arrhythmia. At a median follow-up of 12 months, the overall cardiac mortality rate was 33%, and 40 of 46 deaths occurred within 6 months following DCM diagnosis. A multivariate Cox regression analysis identified several independent cardiac death predictors, including an age of 12 months to 5 years (hazard ratio [HR] 2.799; 95% confidence interval [CI] 1.160–6.758; p = 0.022) or 10–15 years (HR 3.617; 95% CI 1.336–9.788; p = 0.011) at diagnosis, an elevated serum alanine aminotransferase (ALT) concentration (≥51.5 U/L) (HR 2.219; 95% CI 1.06–4.574; p = 0.031), and use of mechanical ventilation (HR 4.223; 95% CI 1.763–10.114; p = 0.001). Conclusion: The mortality rate of primary DCM without transplantation is high. Age, an elevated serum ALT concentration, and the need for mechanical ventilation predict mortality in patients with primary DCM, providing new insights into DCM risk stratification.